Association between High Sensitivity C-Reactive Protein (hs-CRP) Levels and Cognitive Impairment in Elderly Patient with Type 2 Diabetes Mellitus: A Systematic Review - Ida Bagus Oka Garbhajana; Anak Agung Ayu Meidiary; Anak Agung Ayu Putri Laksmidewi (UMI Medical Journal, 2025)
Background: HER2-positive breast cancer (BC) is known for its aggressive behavior and increased risk of brain metastases (BM), which worsens patient prognosis and limits therapeutic options due to the blood brain barrier (BBB). This study systematically evaluates HER2 overexpression as a predictive factor of BM in breast cancer patients through a Systematic Literature Review (SLR) and visualizes global research trends using VOSviewer. This systematic review assessed the relationship between serum hs-CRP levels and cognitive impairment in elderly T2DM patients, exploring its potential as an early screening biomarker. Methods: This systematic review was conducted in accordance with the PRISMA 2020 guidelines. PubMed, Scopus, and Google Scholar were systematically searched for studies published between January 2017 and March 2025. Observational studies involving patients aged ≥60 years with T2DM that reported both hs-CRP levels and cognitive outcomes were included. Study selection, data extraction, and methodological quality assessment using the Joanna Briggs Institute (JBI) critical appraisal tool were performed independently by two reviewers. Due to heterogeneity in study design, cognitive assessment tools, and hs-CRP reporting, findings were synthesized narratively. Results: Most studies showed that higher hs-CRP levels were associated with mild cognitive impairment and poorer executive or memory function in elderly T2DM patients. Some evidence indicated that hs-CRP elevation may precede measurable cognitive decline, suggesting its role in early neuroinflammation. Conclusion: Elevated hs-CRP is consistently linked to cognitive dysfunction in elderly T2DM patients and may serve as a practical biomarker for early detection. Further longitudinal and interventional studies are needed to establish causality and diagnostic thresholds.